PENGARUH MEDIA AUDIO VISUAL TERHADAP TENDANGAN YOKO GERI KEKOMI - Irvan, Irvan; G Simanjuntak, Victor; supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to determine the effect of audio-visual media to yoko geri kekomi in SMK Negeri 1 Sambas west Borneo Province. The metode used was exsperimental. Exsperimental from using one group pretest-posttest design. Intake of this study using purposive sampling technique with a number of 24 people. Data analysis was performed by t-test analysis. From the test result are known yoko geri kekomi kick thitung> ttabel (10,09>2,06) can be concluded that the hypothesis is accepted, which means there is influence. There is a change in the test kicks yoko geri kekomi increase of 14,58%. This is based on test result yoko geri kekomi kick after treated (treatment), where the mean possttest langer than the mean pretest (19,48>17).Keywords : Media audio Visual, Yoko Geri Kekomi Kick In KarateÂ